CSR orientation incongruence and supply chain relationship performance—A network perspective. Issue 2 (29th September 2020) - Liu, Yi; Jia, Xingping; Jia, Xingzhi; Koufteros, Xenophon
Abstract: Firms' commitment to corporate social responsibility (CSR) can be a crucial factor in supply chain partnerships. This study examines the effect of CSR orientation incongruence on relationship performance. Drawing on the congruence theory literature, we posit that a firm's relationship performance may suffer when there is incongruence between the levels of CSR orientations of supply chain partners. Furthermore, we adopt a network perspective and argue that certain characteristics of a firm's egocentric social network (i.e., network centrality and network diversity) may moderate the linkage between CSR orientation incongruence and relationship performance. Our empirical study, which is based on dyadic data, indeed reveals that a firm's relationship performance is adversely affected when the firm and its major supply partner have incongruent levels of CSR orientations. Such a negative effect is moderated by the firm's egocentric social network. Specifically, the negative impact of incongruent CSR orientation is heightened if the firm occupies a central position in the egocentric network. Network diversity, however, plays a contrasting role as a firm's relationship performance may be less susceptible to incongruent CSR orientations when there is access to a diverse social network.